MELACAK DETEKSI FRAUD BERBASIS WHISTLEBLOWING - Arianto, Bambang (Jurnal Akuntansi, Auditing dan Investasi, 2022)
This article aims to elaborate fraud detection efforts through the implementation of a whistleblowing scheme. In this case, whistleblowing is a channel that has been designed in such a way that the public can report various indications of fraudulent practices in both the business and public sectors. The whistleblowing channel is structured as a measure to detect and prevent early fraudulent practices in the public and private sectors. Nevertheless, the implementation of whistleblowing still requires the role of whistleblowers who are accompanied by an anonymous reporting scheme so that they can provide guarantees to reporters of various fraudulent practices. This article uses a literature review approach in elaborating the research topic. This article states that whistleblowing channels are effectively used to detect and prevent various fraudulent practices in all public and business sectors.